Effect of fluorine addition on the structure and properties of high-porous glass ceramics applicable for reconstructive surgery - Sych, O.; Iatsenko, A.; Tovstonoh, H.; Tomila, T.; Yevych, Y. (Functional Materials, 2017)
Effect of fluorine introduction into composition of high-porous glass ceramics based on biogenic hydroxyapatite and glass of the SiO₂-CaO-Na₂O system on structure and properties of the material obtained via doubling the polymer matrix structure has been studied. It is established that during sintering of samples from high-porous glass ceramics at 900°C a partial decomposition and/or interaction of hydroxyapatite with the glass phase occur, that results in forming the multiphase ceramics containing renanite, calcium silicophosphate, calcium pyrophosphate, pectolite and hydroxyapatite. In addition, in the case of fluorine introduction, fluorapatite is formed and sample strength increases by 30 % along with slight decrease in solubility in vitro.